2016
DOI: 10.1021/acs.jpcc.6b03991
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Model Dye/Titania Interface: Geometry of Benzoate on Rutile-TiO2 (110)(1 × 1)

Abstract: Scanned-energy mode photoelectron diffraction (PhD) and ab initio density functional theory (DFT) calculations have been employed to investigate the adsorption geometry of benzoate ([C 6 H 5 COO] -) on rutile-TiO 2 (110)(1×1). PhD data indicate that the benzoate moiety binds to the surface through both of its oxygen atoms to two adjacent five-fold surface titanium atoms in an essentially upright geometry. Moreover, its phenyl (C 6 H 5 -) and carboxylate ([-COO] -) groups are determined to be coplanar, being al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 45 publications
5
14
0
Order By: Relevance
“…A nearly fully covered rutile (110) surface (θ ≈ 0.5 ML) can be prepared by slight heating to ≈370 K and further exposure to adsorbates. , The resulting structure gives rise to a 2 × 2 pattern in a recent low-energy electron diffraction (LEED) experiment . It is reported to diminish rapidly during electron bombardment and end up in a long-term stable 2 × 1 pattern, which is supposed to be identical to the previously reported ones. , Structures that yield a 2 × 2 pattern are clearly seen in scanning tunneling microscope (STM) experiments. ,, Those studies reveal pairwise (sometimes 3-fold) agglomerated benzoate rows, which run in [001] direction.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…A nearly fully covered rutile (110) surface (θ ≈ 0.5 ML) can be prepared by slight heating to ≈370 K and further exposure to adsorbates. , The resulting structure gives rise to a 2 × 2 pattern in a recent low-energy electron diffraction (LEED) experiment . It is reported to diminish rapidly during electron bombardment and end up in a long-term stable 2 × 1 pattern, which is supposed to be identical to the previously reported ones. , Structures that yield a 2 × 2 pattern are clearly seen in scanning tunneling microscope (STM) experiments. ,, Those studies reveal pairwise (sometimes 3-fold) agglomerated benzoate rows, which run in [001] direction.…”
Section: Introductionsupporting
confidence: 53%
“…A nearly fully covered rutile (110) surface (θ ≈ 0.5 ML) can be prepared by slight heating to ≈370 K and further exposure to adsorbates. 12,16 The resulting structure gives rise to a 2 × 2 pattern in a recent low-energy electron diffraction (LEED) experiment. 15 It is reported to diminish rapidly during electron bombardment and end up in a long-term stable 2 × 1 pattern, which is supposed to be identical to the previously reported ones.…”
Section: ■ Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The dissociative adsorption of formic acid, according to LEED, lifted the SCV reconstruction giving a LEED pattern indicative of a bulk-like termination. A recently published surface X-ray diffraction (SXRD) study by Arndt et al 23 has shown that the formate is bound to two surface Fe oct cations through its two carboxylate oxygens, O HCOO , which is consistent with how formate [24][25][26][27][28][29] and more broadly the carboxylate functional group, [30][31][32][33][34][35][36][37] bonds with most surfaces. Moreover, they were able to determine that the formate molecule preferentially binds to one of the two bidentate adsorption sites, the 'tet' adsorption site, with the formate carbon atoms coincident with the 1st subsurface Fe tet in the [110] crystallographic direction, shown in Fig.…”
Section: Introductionmentioning
confidence: 83%